Reasons for discontinuing study : the case of mature age female students with children - Scott, Catherine [Verfasser]; Burns, Ailsa [Verfasser]; Cooney, George [Verfasser] (My University, 1996)
"The research investigated reasons for leaving study amongst a sample of 118 mature age female students with children who had been enrolled at one of three eastern Australian universities. Analysis of questionnaire data revealed three major types of motive for attrition. Firstly, a strong socio-economic class influence was found. Women whose own and/or whose husbands' social class indicators were low tended tp leave study because of a combination of lack of support from family for the mother's study, lack of money, weight of domestic responsibility and lack of knowledge or skills expected at university. Secondly, women who had been enrolled in non-traditional subjects (economics/business/law) were relatively overrepresented amongst the discontinuing students and were particularly likely to cite lack of academic support or staff hostility as a reason for leaving. Thirdly, reasons for leaving study were found to be connected to student's age, suggesting a life style interpretation. Younger women with younger children were likely to leave because of family, financial or child care related reasons. Older women were more likely to leave because of practical difficulties or course dissatisfaction." (author's abstract, IAB- Doku) ((en)) Die Analyse der Befragung von 118 mindestens 30jährigen Studentinnen mit Kindern in Ausbildung ergibt drei Haupttypen von Motiven für einen Studienabbruch: sozio-ökonomische Gründe aufgrund von Schichtzugehörigkeit, fehlende akademische Unterstützung in männerdominierten Studienfächern, altersspezifische Gründe (familiäre Motive bei den jüngeren Studentinnen, studienbezogene bei den älteren). (IAB)
Keywords: I 2.3.5 Australien, Ozeanien; Studienabbruch; Einflussfaktor; Mütter; Student; Frauen; Quantitative Angaben; Australien; 1988-1988